The Best Talk Sdn Bhd - Kalong, Mohd Hisyamuddin; Saplin, Mohammed Ayyub; Abd Kadir, Herman; Hassan, Amran (2016)
On December 2015, our founder Mohammed Ayyub persuaded us to form our business regarding the demands of the counselling services. The increasing of the demands is affecting from the growth of the economic or in other words the increasing of the new company in the country, especially in our state. With the full concerned all the members, finally THE BEST TALK SDN BHD was created. Our company only served according the guideline to form the new business to the entity who wanted our help until they can stand on their own. On 09 February 2016 is the date of our commencement. We located at the menara MAA at kota Kinabalu, why we choose this place because of the centre of the city with the majorities the business are operation. This company are conducted with 4 members which is Mohammed Ayyub bin Saplin as a GM and will in charged the financial department followed by Mohd Hisyamuddin bin Kalong as co-founder and will in charged in human resource department or administration, while in marketing department will control by Herman bin Abd Kadir and the operational department will in charge by Amran bin Hasan. Of course the business plan is created to the bankers in order to get the financial as a our main source of capital. Besides, this business plan also is used for us as a guideline day to day in our operation because all the information, methods and the references are stated in the business plan.